2018
DOI: 10.3390/app8101794
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Raman Scattering of Large Size Hexagonal Bi2Se3 Single-Crystal Nanoplates

Abstract: Bi 2 Se 3 has extensive application as thermoelectric materials. Here, large-scale Bi 2 Se 3 single-crystal hexagonal nanoplates with size 7.50–10.0 μ m were synthesized successfully by hydrothermal method. X-ray diffraction (XRD), scanning electron microscope (SEM), and transmission electron microscope (TEM) were used to characterize the Bi 2 Se 3 nanoplates, which confirm the single-crystal quality and smooth surface morphology with large size. Micro-Raman sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…The phenomenon of redshift of phonon bands at high temperatures might be due to the lattice distortion or volume expansion of the unit cell. [72,73] Moreover, the softening of the phonon modes with temperature is interrelated with the lifetime of strongly interacting optical phonons. Because thermal interaction, which is larger at higher temperature, reduces the mean free path of phonons, the lifetime also decreases, which in turn leads to the increased line width.…”
Section: The Phenomenon Of Diverse Thermal Quenchingmentioning
confidence: 99%
“…The phenomenon of redshift of phonon bands at high temperatures might be due to the lattice distortion or volume expansion of the unit cell. [72,73] Moreover, the softening of the phonon modes with temperature is interrelated with the lifetime of strongly interacting optical phonons. Because thermal interaction, which is larger at higher temperature, reduces the mean free path of phonons, the lifetime also decreases, which in turn leads to the increased line width.…”
Section: The Phenomenon Of Diverse Thermal Quenchingmentioning
confidence: 99%
“…At the lower temperature of 100 K, four characteristics Raman modes (A 2 2u , E 2 g , A 2 1g and A 3 2u ) of Sb 2 Te 3 are clearly distinguishable, whereas A 2 2u and E 2 g Raman modes get merge together toward higher temperatures i.e., 220 K and 300 K. Red shift and peak broadening were observed all the Raman modes (A 2 2u , E 2 g , A 2 1g and A 3 2u ) with the increase in temperature from 100 to 300 K. In general, temperature-dependent Raman spectroscopy is widely used to investigate the thermal expansion, thermal conduction and interlayer coupling [ 15 , 31 , 32 ]. In addition, the peak frequency has a linear dependence with the temperature, which is given by [ 15 ], where ω 0 is the frequency of vibration of these phonon modes at absolute zero temperature, and χ is the first-order temperature coefficient of these phonon modes. It has been reported that thermal expansion and contraction of the crystal and phonon modes may lead to the dependency of the peak position in Raman spectroscopy with temperature [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Reduced dimensionality of these materials has been proven to be one of the most common approaches to minimize the thermal conductivity and to obtain high ZT [ 13 ]. To minimize the thermal conductivity, it is very important to understand the phonon dynamics in this type of material, particularly the phonon–phonon and electron–phonon interactions, all of which have a great impact on the thermoelectric device performance [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the yield of chemical vapor deposition methods is very low in contrast to solvent-based procedures, and they require the use of designated substrates and expensive equipment . In contrast to this, published wet-chemical routes so far yielded either sub-10 nm thin NSs with still rather insufficient lateral sizes of up to 2 μm or those reaching sizes of up to 10 μm but having thicknesses above 10 nm . In this work the focus is laid on the development of a facile wet-chemical procedure to obtain Bi 2 Se 3 NSs with lateral sizes of up to 10 μm without increasing the thickness beyond 12 nm.…”
Section: Introductionmentioning
confidence: 99%